Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Crystalline LaCoO3 perovskite as a novel catalyst for glycerol transesterification - Phadtare, Deepshree; Kondawar, Sharda; Athawale, Anjali; Rode, Chandrashekhar (Molecular Catalysis, 2019)
LaCoO3 perovskite was synthesized using sol-gel method by nitrate and acetate precursors of La and Co with varying molar ratios of La and Co (1:1, 1:2 and 2:1). This was found to be an unique strategy to obtain highly crystalline LaCoO3 perovskite material without using any chelating agent. The variation of precursors was found to influence their crystallinity however, variation in molar ratio in the range of 0.5-2, did not affect the formation of perovskite framework. The formation of pure perovskite phase (around or > 80%) could be achieved by combination of acetate and nitrate precursors while, the combination of acetate- acetate or nitrate- nitrate precursors resulted in low phase purity for the perovskite due to the formation of secondary phases like La2O3 and Co3O4. Very interestingly, such combination of perovskite and pure oxide phases contributed to enhancement of basic sites which catalyzed the glycerol transestrifiaction with DMC (dimethyl carbonate) to GC (glycerol carbonate) and GD (glycidol). Among all the catalysts studied, NAP-2 showed highest efficiency in terms of 98% glycerol conversion and 77% GC and 22% GD selectivities. The highlight of this work is that first step glycerol transesterification with DMC required basic sites of either metal oxide or perovskite but for cascade reaction involving decarboxylation required both metal oxide as well as LaCoO3 perovskite phase.

Heteropolyacids supported on mesoporous AlSBA-15 as efficient catalysts for esterification of levulinic acid - Lucas, Nishita; Gurrala, L.; Athawale, Anjali (Journal of Porous Materials, 2019)
A comparative study of different heteropoly acids supported on mesoporous AlSBA-15 for the synthesis of ethyl levulinate has been undertaken for the first time. The catalysts were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, inductively coupled plasma-optical emission spectrometry, thermo gravimetric analysis, temperature programmed desorption of NH3 and N-2 sorption studies. Insights into crucial parameters for the esterification reactions are also furnished. A distinct correlation was observed between acid density and conversion revealing that the distribution of acidic sites and their accessibility by the reactant moieties plays an important role in determining the overall activity. The effects of various reaction parameters were investigated to enhance the catalytic activity and yield of ethyl levulinate. Under the optimized conditions, levulinic acid conversion of 87.4 mol% and ethyl levulinate selectivity of 100% could be obtained with silicotungstic acid supported on AlSBA-15.